Qualidade das águas de poços subterrâneos do Município Limoeiro do Norte – CE, região semiárida brasileira - Rodrigues, Luma Lorena Loureiro da Silva (Universidade Federal Rural do Semi-Árido, 2018)
In the Ceará state’s region of Limoeiro do Norte, underground water resources are one of the main sources of water for supplying urban and rural communities. Due to population growth, expansion of the agricultural and industrial sector associated with irregular rainfall rate, the exploitation of groundwater has been boosted and may change its quality. Thus, the objective of this work was to assess the physicochemical and microbiological characteristics, as well as the potential of salinization and sodification of groundwater in Limoeiro do Norte, Ceará, semi-arid region of the Northeast. Six water wells were selected for the study, all of them used for irrigation and human consumption. Water’s characteristics analyzed were: temperature, turbidity, pH; CE, K+, Na+, Ca+2, Mg+2, Cl-, SO4-2, CO3-2 and HCO3-, also water hardness and SAR. Microbiologically, total and thermotolerant (Fecal) Coliforms were analyzed. For all of the water analyzes, a completely randomized experimental design with 5 replicates was used, and means of data were compared by Tukey test (p < 0.05). The ionic classification was performed by Piper Diagram and the salinity risk using the U.S.S.L (United States Salinity Laboratory) Diagram using Qualigraf software. Based on the mean concentration of chemical elements (mmolc L-1) in groundwater, we have the following quantification: Na+ > Ca+ > Mg+ > K+ for cations and, an anion variation between the wells, being 1, 3 and 4 Cl- > HCO3- > SO4-2 > CO3-2 and wells 2, 5 and 6 HCO3- > Cl- > SO4-2 > CO3-2. Water from wells 1, 2, 3 and 6 were considered as alkaline and moderately hard; wells 4 and 5 were classified as hard and soft, respectively. With the exception of well 6, classified as freshwater, all other wells were classified as brackish water. Considering water for irrigation, wells 1, 2 and 3 have severe use restrictions by both SAR and Na+, and salinity and sodium tolerant crops should be recommended. In the general classification, water from wells 1, 3 and 5 were classified as mixed sodium; 2 and 6 as sodium-bicarbonate; and 4 as mixed chlorinated. All wells were classified with high salinity, with medium to low sodification risk. With the exception of Na+, no chemical risk was detected for human consumption. Contamination by total coliforms was detected in all wells, however, thermotolerant coliforms were detected in well 5.
Monografia
Keywords: Dureza; Salinidade; Sodificação; Diagrama de Piper; Coliformes; Hardness; Salinity; Sodification; Piper’s diagram; Coliforms; CIENCIAS AGRARIAS::AGRONOMIA